2023
DOI: 10.3390/ani13030448
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MTNR1A Genetic Polymorphisms and Their Association with the Reproductive Performance Parameters in Two Mediterranean Sheep Breeds

Abstract: Sheep farming plays an important economic role, and it contributes to the livelihoods of many rural poor in several regions worldwide and particularly in Tunisia. Therefore, the steady improvement of ewes’ reproductive performance is a pressing need. The MTNR1A gene has been identified as an important candidate gene that plays a key role in sheep reproduction and its sexual inactivity. It is involved in the control of photoperiod-induced seasonality mediated by melatonin secretion. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…Finally, it is interesting to compare our results on the goat species with the most recent advances in the ovine species. Indeed, even in sheep, the most investigated SNPs are rs430181568 (at position g.17355452) and rs406779174 (at position g.17355458) [30]. These are the same polymorphisms that were specifically investigated in our study.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Finally, it is interesting to compare our results on the goat species with the most recent advances in the ovine species. Indeed, even in sheep, the most investigated SNPs are rs430181568 (at position g.17355452) and rs406779174 (at position g.17355458) [30]. These are the same polymorphisms that were specifically investigated in our study.…”
Section: Discussionmentioning
confidence: 59%
“…In sheep species, a polymorphism at the g.17355452 position was found following MnlI enzymatic digestion, which showed a strong link with reduced reproductive seasonality in different Mediterranean breeds. This was shown to be associated with a mutation at the g.17355358 position, which led to an amino acid substitution of Val to Ile, causing a modification in the melatonin signal transmission [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that polymorphisms in the MTNR1A gene are associated with reproductive seasonality [ 22 , 29 ], reproductive resumption [ 10 ], sexual activity of rams [ 30 ], and lamb birth weights [ 31 ] among sheep. In addition, MTNR1A is expressed in the hypothalamus, pituitary gland, and ovaries in several sheep breeds [ 10 , 11 , 32 ], and a significant difference in the expression of the MTNR1A gene in the hypothalamus between sheep exhibiting year-round estrus and sheep exhibiting seasonal estrus has been reported [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, melatonin serves to modulate gene expression associated with steroidogenesis, differentiation, and luteinization of granulosa cells. 31 This hormone safeguards the integrity of oocytes and granulosa cells through its specific receptors, MTRN1A and MTRN1B2, by actively scavenging reactive oxygen species (ROS) and regulating apoptosis-related genes, thus preventing apoptosi. 32 …”
Section: Mechanisms Involved In the Production And Secretion Control ...mentioning
confidence: 99%